Pengaruh Lokasi Usaha dan Strategi Pemasaran Terhadap Penjualan pada Brother Perfume 1 Kota Sukabumi - Aziz, Abdul; Ahmad, Deni (CV. Kalimasada Group, 2024)
This research was conducted at Brother Perfumer 1 Sukabumi City. The purpose of this research is to determine the effect of business location and marketing strategy on sales at Brother Perfume 1 Sukabumi City. The research method used is descriptive and associative methods. The population in this study were consumers who made transactions at Brother Perfume 1 Sukabumi City and the sample used was 100 people obtained using non-probability sampling with a accidental sampling approach and using the Yamane formula. To test the research instrument, use the validity test, reliability test and classical assumption test, then for influence analysis use Spearman Rank correlation analysis, coefficient of determination analysis, multiple linear regression analysis, partial t test and simultaneous f test. Based on the results of the correlation analysis that has been carried out, it shows that the correlation value of business location to sales is 0.625 or 62.5% which is included in the strong correlation category because it is in the interval 0.600-0.799 and the correlation value of marketing strategy to sales is 0.559 or 55.9% which is included medium correlation category because it is in the interval 0.400-0.599. Based on the determination analysis that has been carried out, it shows the large contribution of the influence of business location and marketing strategy on sales as indicated by the R Square value of 0.485 or 48.5%, the remaining 51.5% is influenced by variables other than business location and marketing strategy which were not researched by researcher